Konsep Pendidikan Karakter Anak Perspektif Pendidikan Islam Menurut Ibn Qayyim Al-Jauziyyah - Makmudi Makmudi (Jurnal Dirosah Islamiyah, 2022)
The main problem that causes character crises in children is not making faith a philosophical basis in education. So that has implications for the euphoria of excessive freedom. The child's success is only seen from the point of view of the child's academic success. Meanwhile, ethical, moral, and character values ​​have received less serious attention. Therefore, although students excel in terms of their intelligence quotient (IQ), but emotionally quotient (EQ) children experience a very worrying character crisis. In this context, the existence of children's character education is considered very important for the next generation of the nation as an integral part of life and life. The purpose of writing this research is to find out and analyze the thoughts of Ibn Qayyim al-Jauziyyah about the concept of character education for children from the perspective of Islamic education. Children's character education is considered important, because in Islam morality or character is the realization of religious values ​​that collect all goodness and is the foundation of all goodness and the key to achieving all goodness. Education has three elements that exist in humans, namely physical (psychomotor) elements which include body development, skills (skills) and sexual education, spiritual (affective) elements which include fostering faith, morals and irada (will), reason (cognitive) elements. which includes the development of intelligence and the provision of knowledge. The process of character education according to Ibn Qayyim Al-Jauziyyah focuses on four important things, namely: 1. The importance of introducing children to monotheism to Allah, 2. The need to teach children the basics of religious teachings, 3. Teaching and familiarizing children with good ethics and morals, 4. Exemplary, 5. Educational praise and punishment.